Mediation of the parental education gradient in early adult mortality by childhood adversity: a population-based cohort study of more than 1 million children - Leonie K Elsenburg, PhD; Andreas Rieckmann, PhD; Tri-Long Nguyen, PhD; Jessica Bengtsson, PhD; Anne-Marie Nybo Andersen, ProfMD; David Taylor-Robinson, ProfPhD; Theis Lange, ProfPhD; Naja Hulvej Rod, ProfDMSc (Elsevier, 2022)
Summary: Background: Children born into disadvantaged socioeconomic circumstances are more likely to experience both adversity during childhood and premature mortality. The aim of this study was to investigate how much of the parental education gradient in early adult mortality is explained by exposure to childhood adversity. Methods: We used data from the nationwide register-based Danish Life Course cohort study. Our sample consisted of all individuals born between Jan 1, 1980, and Dec 31, 2001, who did not emigrate or die before age 16 years, and for whom information on parental education level was available. These individuals were followed up for mortality from age 16 years until Dec 31, 2018. Highest attained parental education level at birth was divided into low (≤9 years), medium (10-12 years), and high (>12 years) according to years in education. Individuals were assigned to one of five childhood adversity trajectory groups based on their annual exposure between age 0 and 16 years to a broad selection of adversities in three dimensions: material deprivation, loss or threat of loss in the family, and family dynamics. Childhood abuse was not included. The association between parental education level and mortality was assessed with a Cox proportional hazards model. To assess the magnitude of mediation of this association by childhood adversity, we used counterfactual mediation analysis and an Aalen additive hazards model. Analyses were unadjusted and adjusted for parental origin and parental ages at birth. Findings: Our sample consisted of 1 278 156 individuals followed up from birth until age 16-38 years. The sample comprised 655 633 (51·3%) men and 622 523 (48·7%) women, and 1 243 981 (97·3%) participants were of European descent. During follow-up, 5387 deaths were registered. Compared with the high parental education group, we calculated a total effect equal to 8·7 additional deaths (95% CI 6·6-10·9) per 100 000 person-years in the medium parental education group and 31·9 (28·5 to 35·2) per 100 000 person-years in the low parental education group. Mediation through childhood adversity trajectories accounted for 41·5% (95% CI 8·0-67·5) of the additional deaths in the medium parental education group and 46·4% (32·9-58·8) of the additional deaths in the low parental education group. The results were similar when adjusting the analyses for sociodemographic factors. Interpretation: The experience of childhood adversity seems to be an important mediator of the association between parental education and mortality in early adulthood. Interventions reducing the exposure to childhood adversity might thus reduce the parental education gradient in early adult mortality. Funding: Netherlands Organisation for Health Research and Development.